Investigation of the bimodal character of RHEED intensity oscillations during homoepitaxial growth of Si/Si(100) - Sokolov, А. S. (Двадцатая Всероссийская конференция студенческих научно-исследовательских инкубаторов, г. Томск, 2–5 мая 2023 г.)
This paper presents a study of the bimodal character of the intensity oscillations of diffraction patterns obtained by the method of fast reflected electron diffraction during the epitaxial growth of Si on a Si(100) substrate. The dependence of the nature of oscillations of the intensity of diffraction patterns during the epitaxial growth of Si on Si(100) is shown in a wide temperature range of the substrate.